Int J Foot Ankle 2018
DOI: 10.23937/ijfa-2017/1710009
|View full text |Cite
|
Sign up to set email alerts
|

Playing Basketball on Wooden and Asphalt Courts-Does Court Surface Affect Foot Loading?

Abstract: This study aimed to examine the influence of court surface on foot loading when executing typical basketball tasks. Thirteen male basketball players performed three basketball-related tasks: Layup, jump shot, and maximal effort sprint on wooden and asphalt courts. In-shoe plantar loading was recorded during the basketball movements and peak force (normalised to body weight) was extracted from eight-foot regions. Perceptions of discomfort at the ankle, knee, and back were surveyed using a 10-cm visual analogue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Additionally, studies have also found that the quality and type of playing surface affects several physiological and biomechanical aspects of propulsion, in particular in lower-classed players (Crespo-Ruiz et al, 2011). Temporary wooden basketball courts have been found to result in the requirement of higher peak forces to generate movement (Kong et al, 2018). Therefore, dependent on the cushioning and the resistance of the court, players would be required to expend more energy to propel the wheelchair.…”
Section: Ha In Wheelchair Basketballmentioning
confidence: 99%
“…Additionally, studies have also found that the quality and type of playing surface affects several physiological and biomechanical aspects of propulsion, in particular in lower-classed players (Crespo-Ruiz et al, 2011). Temporary wooden basketball courts have been found to result in the requirement of higher peak forces to generate movement (Kong et al, 2018). Therefore, dependent on the cushioning and the resistance of the court, players would be required to expend more energy to propel the wheelchair.…”
Section: Ha In Wheelchair Basketballmentioning
confidence: 99%
“…Another study [95] evaluated the extent to which foot loading is affected by the court surface (wood or asphalt) on which basketball is played. For this purpose, three tasks related to basketball were performed, both on wood and asphalt courts, by the study participants: layup, jump shot, and maximal effort sprint.…”
Section: Pedar In Sports Applicationsmentioning
confidence: 99%
“…The application of Pedar-X for basketball players [95] might evolve mainly three new directions: obtaining also kinematic data, such as sprint speed or jump height; evaluation of the stiffness for various court surfaces (besides wood and asphalt, used in the study); taking into account not only the plantar forces, but also the joint kinetics.…”
Section: Challenges and Open Issuesmentioning
confidence: 99%